Analisis Penggunaan Energi Listrik Untuk Peluang Hemat Energi Di Tiara Residence - Lubis, Dona Tiara; Novalianda, Sari; Mawardi, Mawardi; Yudisha, Nabila (Universitas Medan Area, 2024)
An energy audit needs to be carried out to calculate energy consumption in buildings. This activity is a form of energy management which aims to meet national energy needs in accordance with long-term energy management policies, including Law no. 30 of 2007, concerning energy. This research uses data on the use of electrical energy at the Tiara Residence boarding house. The results of the energy audit serve as a reference for increasing profits from the boarding house business by saving on monthly electricity usage costs based on the amount of electricity consumption paid. This research was carried out by calculating the energy consumption intensity (IKE) value with influencing variables including energy consumption (kWh) per square meter (m2) per month. Based on the results obtained, the monthly power consumption is 1049 kWh-1231 kWh at a cost of Rp. 1,576,836-Rp. 1,852,473, then the IKE value is calculated and it is known that the efficiency level of energy use is in the efficient category in February, March, July, August, September and October, while in January, April, May, June it is categorized as very efficient. Apart from that, there are opportunities to save from installed electrical equipment by applying special behavior to the equipment.